IN SILICO ANALYSIS AND MOLECULAR DOCKING OF CURCUMIN ANALOGS AND ANTIFUNGAL COMPOUNDS AGAINST CRITICAL PROTEINS OF ASPERGILLUS SPECIES: A COMPARATIVE INVESTIGATION - Mohammad Javad Javid-Naderi; Hossein Zarrinfar; Tahany Al-Shemary (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aspergillosis, primarily caused by Aspergillus fumigatus, is a fungal infection that affects immunocompromised patients. With the increasing resistance to antifungal azoles caused by their overuse, there is a need for new therapies. This study focused on identifying key proteins that play a critical role in medication resistance and infection propagation in Aspergillus, with the aim of discovering new treatments. Six essential proteins have been identified in Aspergillus following a comprehensive literature review. These proteins comprise Cyp51A and Cyp51B enzymes, as well as MDR1-4 efflux pumps. In silico homology modeling and molecular docking analyses were performed using SWISS-MODEL and Autodock Vina in PyRx to estimate the inhibitory activity of candidate drugs against these proteins. These compounds were also tested for toxicity using the ProTox-II and pkCSM servers. Drug-likeness and ADME properties were assessed using the SwissADME server. The prediction of the PASS and Molinspiration webservers determined the pharmacological and biological activities of the compounds. The three ligands, pramiconazole, curcumin difluorinated (CDF), and curcumin, exhibited significant binding affinity to target proteins, indicating their potential to inhibit the overexpression of Aspergillus target protein genes. These compounds have demonstrated superior medicinal properties and lower toxicity compared to standard drugs used against Aspergillus. In conclusion, through molecular docking and in silico screening, pramiconazole, CDF, and curcumin have shown improved pharmacological properties compared to current treatments for aspergillosis. These compounds hold promise as alternative treatments that could potentially overcome antifungal resistance.